Indonesia ORIENTASI FILOSOFIS HAKIM DALAM MEMUTUSKAN PERKARA REHABILITASI BAGI PECANDU ATAU PENYALAH GUNA NARKOTIKA BAGI DIRI SENDIRI - Teguh Hartono; Vadira Hanami; Fanniya Dyah Prameswari (Faculty of Law, Universitas Slamet Riyadi, 2023)
This article wants to analyze the judge's verdict orientation of the rehabilitation case for addicts or drug abusers. Far from the construction of rehabilitation laws in Indonesia, there is a diffusion of norms between the health and the criminal approach. Legal research with a constitutional and case approach at the state court in Bali and Yogyakarta. A comparative approach of law with other countries. The study suggests that judges are more likely to drop sentences in prison sentences than in rehabilitation, even though the accused meets the criteria of narcotics law and a writ of avoidance of the Supreme Court. The complaint was merely a recommendation that judges were not required to comply with, as was the case in Portugal and Australia. The judge's paradigm of self-initiated drug abuse, like narcotics crimes, is similar in Vietnam. Whereas the philosophical orientation of the judges in deciding the issue of rehabilitation should be based on principles of humanity and justice as governed by the just and civilized precepts of humanity and the precepts of social justice for all peoples of Indonesia. The judge is required to consider the report on the results of the conviction of both criminal and criminal action to the perpetrator of criminal narcotics. Also, future prescriptions for self-initiated drug abuse recovery should be changed with a health approach, drawing a firm line of distinguishing from narcotics crimes. Process in court with a fast trial, including an arrangement for arrest, was held in a designated rehabilitation facility or hospital.